A ordinary fact tale analytical - psycho pedagogy and subjectivity - Rebelo, Teresa; Bernateau, Isée (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
Through the case of Wu-Ying, a psychotic teenager, we are trying to show what paths the psychic link work can borrow. The choice oi a transitional area to three associating a French teacher and a psycho pedagogue - all two clinician psychologists -and the company ot an original literary work, Feather by Henri Michaux, have allowed Wu-Ying to subjective his history, thanks to the dynamic-game of passivity and drive activity.